2013
DOI: 10.1017/s000711451300007x
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory potential of phenolic compounds in grape juice concentrate (G8000™) on 2,4,6-trinitrobenzene sulphonic acid-induced colitis

Abstract: Chronic inflammatory bowel disease is characterised by an up-regulation of the synthesis and release of a variety of pro-inflammatory mediators leading to excessive tissue injury. Flavonoids are able to inhibit enzymes and/or due to their antioxidant properties regulate the immune response. The goal of the present study was to evaluate the mechanisms of action of phenolic compounds present in grape juice on 2,4,6-trinitrobenzene sulphonic acid (TNBS)-induced colitis. A total of forty-one male Wistar rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
1
27
0
2
Order By: Relevance
“…The GELNs‐mediated interspecies information transfer is proved to be functional, protecting mice against DSS‐induced colitis. The protective effect on TNBS‐induced colitis has also been observed in grape juice containing GELNs in another research . In vitro study showed that the uptake of GELNs promoted Lgr5+ intestinal stem cell proliferation as well as subsequent intestinal organoid formation, which indicated that the amelioration of mouse intestinal inflammation may be at least partly because of the enhancement of epithelial reconstitution.…”
Section: Therapeutic Potential Of Exosome In Inflammatory Bowel Diseasesupporting
confidence: 53%
“…The GELNs‐mediated interspecies information transfer is proved to be functional, protecting mice against DSS‐induced colitis. The protective effect on TNBS‐induced colitis has also been observed in grape juice containing GELNs in another research . In vitro study showed that the uptake of GELNs promoted Lgr5+ intestinal stem cell proliferation as well as subsequent intestinal organoid formation, which indicated that the amelioration of mouse intestinal inflammation may be at least partly because of the enhancement of epithelial reconstitution.…”
Section: Therapeutic Potential Of Exosome In Inflammatory Bowel Diseasesupporting
confidence: 53%
“…However, HF-feeding did not increase mRNA markers of inflammation in the ileum or proximal colon or IAP activity in duodenal mucosa after 16 weeks. In contrast, other research has shown that feeding non-physiological levels of saturated fat triggers intestinal inflammation that contribute to increase systemic inflammation and insulin resistance, possibly due to intestinal dysbiosis and barrier dysfunction [713, 18, 19, 6870]. …”
Section: Discussionmentioning
confidence: 99%
“…CTRL and Cd groups were treated with drinking water by gavage during the same experimental period. The grape juice group was not included into this experimental design because our research group has evaluated the protective potential of grape juice under different paradigms and the results have revealed that animals treated with grape juice only did not change such biological parameters investigated (Pires et al 2013;Paiotti et al 2013;de Jesus et al 2014).…”
Section: Animals and Experimental Designmentioning
confidence: 99%